HUBUNGAN TINGKAT KEPATUHAN PENGGUNAAN OBAT TERHADAP KUALITAS HIDUP DAN OUTCOME TERAPI PASIEN DIABETES MELITUS TIPE 2 DI RSUD DR. MOEWARDI SURAKARTA - Neha Azziza Cherrysha Alifia; Kharisma Jayak Pratama; Anna Fitriawati (Universitas Imelda Medan, 2026)
Type 2 Diabetes Mellitus is a chronic disease that requires long-term and continuous management. One of the key factors influencing treatment success is patient adherence to medication. Good adherence can improve quality of life and optimize therapeutic outcomes, while poor adherence often leads to unfavorable outcomes, such as uncontrolled HbA1c levels. This study aimed to determine the relationship between medication adherence and both quality of life and therapeutic outcomes among Type 2 Diabetes Mellitus patients at Dr. Moewardi General Hospital in Surakarta. This study employed an observational design with a cross-sectional approach. A total of 98 patients were recruited using purposive sampling. The instruments used included the MMAS-8 questionnaire to measure medication adherence, the WHOQOL-BREF questionnaire to assess quality of life, and laboratory HbA1c data to evaluate therapeutic outcomes. Data were analyzed using Pearson correlation and chi-square tests. The results showed that most patients had moderate adherence (64,3%), moderate quality of life (100%), and uncontrolled therapeutic outcomes. There was a significant relationship between medication adherence and quality of life (p = 0.015; r = -0.246), but no significant relationship between adherence and HbA1c therapeutic outcomes (p = 0.524). Other factors such as lifestyle, complications, and social support also influence therapeutic success.